Kesiapan Sekolah Dasar Dalam Menjalankan Pembelajaran Tatap Muka (PTM) Terbatas di Era New Normal - Fina Silfia; Siti Epon Nurmila (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
In order to organize learning during the adaptation period for new habits (new normal), due to the COVID-19 outbreak, various suitable strategies are needed by remaining guided by active, creative, and fun learning. Therefore, this study aims to determine the readiness of elementary school educators in conducting limited face-to-face learning (PTM) in the new academic year 2021/2022. A total of eight teachers have been interviewed regarding this Limited PTM. The results show that teachers are ready to welcome limited PTM which will begin in the new academic year 2021/2022. This readiness is inseparable from the Tangerang Regent's Instruction Number 17 of 2021 concerning the implementation of restrictions on community activities at level 1 Corona Virus Disease 2019 in Tengerang Regency, in addition to the availability of facilities and infrastructure that are adapted according to health protocols and also the readiness of teacher competencies in preparing various media, strategies, activities and games to facilitate learning both synchronously and asynchronously.